Update in Chronic Obstructive Pulmonary Disease 2016 - Allinson,JP; Wedzicha,JA (AMERICAN JOURNAL OF RESPIRATORY AND CRITICAL CARE MEDICINE, 2017)
Chronic obstructive pulmonary disease (COPD) describes a predominantly smoking-induced small airway and/or emphysematous disease associated with airflow limitation. Considered progressive, irreversible, and responsible for substantial morbidity and mortality worldwide, COPD remains the subject of vigorous study, and advances made during 2016 are already reflected in the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 guidelines (1). Researchers continue to explore strategies, pharmacological or otherwise, to improve the lives of those who have developed this condition; and it is hoped, by improving phenotyping of this heterogeneous disease, that we might ultimately deliver personalized medicine. Debate remains over how to identify undiagnosed COPD in individuals who would benefit from intervention, while avoiding overdiagnosis, and these controversies perhaps highlight shortcomings in accepted disease definitions. Not unrelatedly, renewed interest has emerged in explaining why some individuals develop COPD and identifying the formative stages of COPD development.